1997
DOI: 10.1002/1521-396x(199709)163:1<47::aid-pssa47>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of ZnTe, CdTe, CdHgTe and HgTe Crystals from Micromechanical Investigation

Abstract: On the basis of an analysis of indenter penetration diagrams some mechanical properties of surface layers of bulk AIIBVI compounds were investigated. These crystals were grown from the melt and vapour phase. Values of Young's modulus, activation volume of microindentation, parameter of hysteresis loss were determined. The analysis of the residual deformation during microindentation permitted to evaluate the degree of covalent bond “stiffness”. An original combination of the mechanical properties of the investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…19 and previous E avg values measured for Bridgman grown bulk Hg 0.8 Cd 0.2 Te. 17 The experimental E avg values agree with the E Voigt average because the isostrain Voigt model is more appropriate than other average modulus models since as the nanoindentation tip deforms the crystal surface it induces strains locally, which result in nearly uniform strains around dislocations. Figure 3 clearly shows that the hardness values obtained below an indentation contact depth of ;300 nm increase with decreasing indentation contact depth for all three HgCdTe samples.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…19 and previous E avg values measured for Bridgman grown bulk Hg 0.8 Cd 0.2 Te. 17 The experimental E avg values agree with the E Voigt average because the isostrain Voigt model is more appropriate than other average modulus models since as the nanoindentation tip deforms the crystal surface it induces strains locally, which result in nearly uniform strains around dislocations. Figure 3 clearly shows that the hardness values obtained below an indentation contact depth of ;300 nm increase with decreasing indentation contact depth for all three HgCdTe samples.…”
Section: Resultssupporting
confidence: 53%
“…The determination and control of mechanical properties in MEMS structures can be the decisive factor in the successful realization and subsequent performance, reliability, and long-term stability of devices. The hardness of bulk HgCdTe has been the topic of significant research: [8][9][10][11][12][13][14][15][16][17][18] however, investigations of the parameter that determines the mechanical performance of the material, that is the modulus of elasticity, are very limited for HgCdTe. 17,19 The mechanical properties of bulk materials as well as thin films are increasingly being determined using depth sensing indentation (DSI), [20][21][22][23][24][25] which is (Received October 17, 2005; accepted January 19,2006) generally referred to as nanoindentation.…”
Section: Introductionmentioning
confidence: 99%
“…Available experimental data of Young's modulus for MCT, which are included in Table 8.3, originate from microindentation measurements of Kurilo et al [75] for bulk crystals (x = 0, 0.2, 1.0) and nanoindentation measurements Martyniuk et al [79,80] for MBE, LPE, as well as bulk material (x = 0.3), which are in good agreement with each other. Since the indentation tip while deforming the crystal structure induces strains locally, it produces nearly uniform strains around dislocations and the experimental Young's modulus values are in closer agreement with the Young's modulus values from Voigt rather than Reuss averaging.…”
Section: Elastic Parameter Valuesmentioning
confidence: 56%
“…8. 25 Sharma et al [85], Hv, quenched Schenk and Fissel [86], Hv, quenched Schenk and Fissel [86], Hv, THM Schenk and Fissel [86], Hv, Bridgeman Triboulet et al [87], Hv, THM Barbot et al [88], Hv, THM Fissel and Schenk [96], Hv, THM Cole et al [89], Hv, Bridgeman Andrews et al [90], which may be related to the dependence of hardness on loading velocity and/or loading time [75,96], or significant amounts of creep [80]. In addition, Martyniuk et al [80] have shown that the measured MCT hardness increases with decreasing indentation depth, an effect that is expected to be especially pronounced for soft crystalline materials [97], and that could also contribute to the degree of scatter.…”
Section: Variation With Compositionmentioning
confidence: 99%
“…For example, Si has a shear modulus l that is more than three times that of CdTe. 24,25 Dislocations are more likely to be repelled by a hard substrate material (silicon) and into a softer epitaxial material (CdTe). 26 Thus, even upon reaching the goal of back-thinned Si wafer thicknesses less than the CdTe layer thickness, it is unlikely that TD densities at the epilayer surface would be reduced by the desired two orders of magnitude.…”
Section: Proposed Understandingmentioning
confidence: 58%